1994
DOI: 10.1029/94jb01549
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation and a nontransform ridge offset on the Reykjanes Ridge near 58°N

Abstract: Multibeam bathymetry, deep‐towed side scan sonar, gravity, and magnetic data over a 50 km square area all suggest the presence of a second‐order, nontransform offset on the obliquely spreading Reykjanes Ridge (North Atlantic ocean) near 58°N latitude. It is the first such offset to be recognized on the Reykjanes Ridge. This region is characterized by a shallow median valley containing en echelon axial volcanic ridges (AVRs) similar to those found on more northerly parts of the Reykjanes Ridge. The side scan so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…1995a, b). They are similar in shape to seamounts near the axis of the East Pacific Rise (Searle 1983;Fornari et al 1987), but fall in the lower end of that size spectrum. The texture seen on TOBI sidescan shows an evolution with age: compare the 'nested' seamounts ( Fig.…”
Section: Constructional Terrainsmentioning
confidence: 76%
See 2 more Smart Citations
“…1995a, b). They are similar in shape to seamounts near the axis of the East Pacific Rise (Searle 1983;Fornari et al 1987), but fall in the lower end of that size spectrum. The texture seen on TOBI sidescan shows an evolution with age: compare the 'nested' seamounts ( Fig.…”
Section: Constructional Terrainsmentioning
confidence: 76%
“…It comprises a conglomeration of myriad, circular mounds, whose diameters range from a few tens of metres to about 500 m. The geometry of the shadows indicates that they are usually less than 50 m high, have rounded summits and no summit craters. TOBI data from the Reykjanes Ridge (Magde & Smith 1995;Mutton & Parson 1993;Parson et al 1993;Searle et al 1994) and elsewhere on the Mid-Atlantic Ridge between 24 ~ and 30~ (Smith et al 1995a, b) show AVRs comprising a similar terrain. Our camera runs (Figs 4 & 5), which are described more fully below, showed that each hummock usually corresponds to an individual pillow flow, with the steep fronts and shallower tops of the flows causing the hummocky morphology.…”
Section: Constructional Terrainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basins are thought to represent non-transform ridge offsets Huestis and Acton, 1997;Searle et al, 1994Searle et al, , 1998.…”
Section: Ridge Segmentationmentioning
confidence: 99%
“…Murton & Parson 1993;Searle et al 1994;Keeton et al 1997, and see Fig. Murton & Parson 1993;Searle et al 1994;Keeton et al 1997, and see Fig.…”
Section: Introductionmentioning
confidence: 96%